Local Language Booklet (BOBA) Can Improve Mothers' Knowledge About Visual Inspection Acetic Acid (IVA) Test Screening: Booklet Berbahasa Lokal (BOBA) Dapat Meningkatkan Pengetahuan Ibu Tentang Skrining Inspeksi Visual Asam Asetat (IVA) Test - Usman, Hastuti; Sumiaty, Sumiaty; Silfia, Niluh Nita; Longulo, Olkamien Jesdika; Asrawaty, Asrawaty; Nazma, Tantri Ainun (Napande: Jurnal Bidan, 2024)
Background: Indonesian health survey data in 2023 obtained IVA Test screening coverage for Central Sulawesi province as much as 91.1% did not screen and those who screened were approximately 8.9%. Purpose: To determine the effect of the BOBA Booklet on mothers' knowledge about VIA Test Screening in Tondo Village, Palu City. Methods: With a population of 542 people and a sample of 61 WUS aged 30-49 years, this study used the Pre-Experiment method with a one-group pre- and post-experiment design. The sampling method is Simple Random Sampling. This study used the Wilcoxon Test to conduct the analysis.  Results:  Based on univariate analysis, it was found that 95.1% of almost all mothers had good knowledge after being given the BOBA Booklet. The results of the Wilcoxon test analysis obtained a p-value of 0.000 because the p-value <0.05. Hence, there is a significant effect of the provision of the BOBA Booklet on increasing maternal knowledge about the VIA Test Screening. Conclusion: Local Language Booklet (BOBA) can increase mothers' knowledge about IVA test screening. So it is recommended that health workers in the Talise Health Center working area increase the understanding of related mothers about screening by using Liflet or other reading media